Health Policies Based on Patient Satisfaction: A Bibliometric Study - Mayra Soledad Grasso (MDPI AG, 2021)
Healthcare decision-makers increasingly face a changing and ever-evolving landscape, forcing them to formulate public policies based on the results from different scientific investigations. This article evaluates the field of research on patient satisfaction as a basis for health policies. The analysis was carried out with a sample of 621 articles published between 2000 and 2020 in the Scopus database. The world’s largest producer and research co-operator on patient satisfaction and health policy was the United States. However, the most prolific authors, institutions, and journals are of British origin. Regarding the themes, we find that, in economic and management matters, scientific production is scarce. To study the evolution of keywords, we divided the study period into two periods of an equal number of years. In both sub-periods, the keyword “Human” stands out. In the second sub-period, the word “Perception” stands out, which indicates the current attention paid to the patient’s opinion.